(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the effectiveness of a multimedia-based mobile application designed to promote daily wellness exercises among female university students. A preliminary survey was conducted among the students, which revealed that while many of them expressed a strong interest in engaging in health-promoting physical activities, they lacked knowledge about appropriate exercise routines and daily workout norms. A specially developed mobile app, made available through the Google Play Market, was used to support the development of a healthy lifestyle among these students. During the experimental phase, selected students were placed into formative groups and provided access to the application. Observational results showed that 80% of the participants found the "My Wellness Exercises – My Healthy Lifestyle" app to be highly convenient and reported significant improvements in their health habits.